2008
DOI: 10.1177/1077559508316042
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Abused Children's Access to Evidence-Based Treatment: Diffusion via Parents as Consumers

Abstract: This investigation evaluated an experimental protocol employed by nurses with parents to increase access to evidence-based mental health treatment for children who are suspected victims of abuse. The protocol was compared with typical services during forensic medical examinations, first in a quasi-experimental design, then as a randomized controlled trial. In both studies, the protocol produced a significant increase in parental reports of having discussed evidence-based treatment during a mental health appoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…We found 19 eligible articles representing 19 studies [13, 14, 4662] (one article reported on two different studies [55] and another two articles [51, 60] reported outcomes for the same trial). These studies represent 18 strategies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found 19 eligible articles representing 19 studies [13, 14, 4662] (one article reported on two different studies [55] and another two articles [51, 60] reported outcomes for the same trial). These studies represent 18 strategies.…”
Section: Resultsmentioning
confidence: 99%
“…No study addressed the moderators of harms. The evidence base included RCTs (some of which were cluster RCTs) [13, 14, 4648, 50, 51, 53, 5562], (nonrandomized) controlled clinical trials (CCTs) [52, 54], interrupted time series [49], and cohort designs [55]. Full evidence tables for articles identified via searches through January 14, 2016, are available at http://srdr.ahrq.gov/projects/530.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations